A carbon tax on agriculture? A CGE analysis for Chile. Issue 2 (2nd April 2020) - Mardones, Cristian; Lipski, Mirko
Abstract : This paper evaluates the implementation of a tax on CO2 equivalent (CO2 eq) emissions produced by the agricultural sector. Computable general equilibrium (CGE) simulations consider tax rates ranging from 5 to 131 USD/ton CO2 eq with sensitivity analyses. We find that a tax applied only to agricultural emissions makes agriculture less competitive and, thus, reduces its production. Real GDP falls from 0.00–0.01% to 0.12–0.40% as a result, and total emissions decline from 0.07–0.10% to 1.79–2.25%. The tax is slightly regressive. We conclude that the tax on just agriculture does not substantially reduce emissions. Indeed, we find it is more efficient to apply the tax across the board, while subsidizing the forestry.